Vivências de idosos em comunidades rurais - Machado, Mariéli Terezinha Krampe (2014)
Life expectancy in Brazil and in the world is increasing considerably and several scholars warn of a significant increase in the number of elderly. Another striking feature of contemporary society is the increase in urban population concentration, which usually centered upon more resources for the maintenance of activities of daily living. In contrast to this reality, we observe detached way of the rural population which finishes counting, most often with family support. Thus the study aimed to know how to live the elderly and the family dynamic interface in a rural context. Evaluate the functionality of the family dynamics using the APGAR scale (Adaptation, Partnership, Growth, Affection, Resolve) family, describe the sociodemographic profile of elderly residents in rural communities and outline the conceptions of experience in family and care in old age manifested by participants. The research scenario was the city of Flor do Sertão, situated in the west of Santa Catarina. The research design was quantitative and qualitative approach of descriptive. For data collection, we used individual interviews applying a questionnaire adapted from the instrument KNOW (Health, Welfare and Aging), the Family APGAR and focus groups ( FG). 156 seniors were interviewed and participated in FG ten elderly of both sexes in every rural micro area of the municipality. The results indicated a predominant age group between 60 to 69 years, most seniors are married, catholic, caucasian origin who were born in rural areas and continue to live there by choice. Most are retired and still working in agriculture and household chores. About 75 % of older people with chronic diseases, 74,3 % hypertension, 11.2% heart disease, lung 7,9 and 3.9 % had diabetes mellitus. Thus, 77 % of elderly people use drugs continuously and 42.1 % use more than two tablets per day. Rely on caregivers aged between 56 and 75 who are usually partner or children. Have good family feature which was evident in 89,5 % of cases . Reported that even though they live far from the headquarters of rural communities in 61.2% of cases, do not feel lonely, as have a network of neighborhood, with technological resources such as the phone shortens distances and some even referendaram pets that do company. The transport and difficult access to some essential services problems were evidenced by the elderly, especially in cases of emergency where depend on relatives or neighbors. Given the potential of the data collected, the study Somara to others, describing the reality of older people living in rural areas and even serve as the basis for the development of health strategies aimed at maintaining quality of life in this population